Palliative care services path in Brazil: historical and current aspects (Research, Society and Development, 2022)
Palliative care emerged in the 1960s, in England. From then, it expanded to different countries in the world. This piece of work aims to discuss the palliative care services path in Brazil over time, in historical and current aspects. The methodology used is integrative literature review. The obtained results constitute three analysis categories: the inicial insertion of palliative care in Brazil, palliative care current conditions in Brazil, and palliative care development institutions in Brazil. In relation to the first one, there is no consensus regarding the entry of pallative attention in the country, neither in time, nor in place. The covered path goes from two services in the 1980s or 1990s, to one hundred ninety-one services, registered by the National Academy of Palliative Care of Brazil, in 2020, with 789 beds, asymmetrically distributed in the different regions. Lastly, the third category regards the organized movements embodied by professionals, who aim to integrate services by creating groups to disseminate the ideas of palliative care in Brazil. As a result, is possible to identify a rising path in these services, a geographical expansion, although asymmetrical, and an organization in the field.